2005
DOI: 10.1364/ol.30.003177
|View full text |Cite
|
Sign up to set email alerts
|

Incoherent light-induced self-organization of molecules

Abstract: ABSTRACT:Although coherent light is usually required for the self-organization of regular spatial patterns from optical beams, we show that peculiar light matter interaction can break this evidence. In the traditional method to record laser-induced periodic surface structures, a light intensity distribution is produced at the surface of a polymer film by an interference between two coherent optical beams. We report on the self-organization followed by propagation of a surface relief pattern. It is induced in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…For instance, it was observed that the free surface of azobenzene polymer films could exhibit induced mass transport if exposed to a light intensity pattern [12]-it undergoes cyclic photoinduced trans-cis isomerization. Spontaneous patterning effects in azo-dye polymer films have already been reported [13] on planar substrates while illuminated by one single laser beam under specific experimental conditions. Since, laser beam parameters are modified by the turbulence, the structure formations inscribed on the thin film change accordingly.…”
mentioning
confidence: 89%
“…For instance, it was observed that the free surface of azobenzene polymer films could exhibit induced mass transport if exposed to a light intensity pattern [12]-it undergoes cyclic photoinduced trans-cis isomerization. Spontaneous patterning effects in azo-dye polymer films have already been reported [13] on planar substrates while illuminated by one single laser beam under specific experimental conditions. Since, laser beam parameters are modified by the turbulence, the structure formations inscribed on the thin film change accordingly.…”
mentioning
confidence: 89%
“…Nunzi and co-workers demonstrated that the use of an incoherent light source is also efficient for the deformation of azopolymer nanospheres 46 and for printing a well-organized pattern at the surface of an azopolymer thin film. 47 Here, we focus our attention on the case of a linearly polarized light.…”
Section: Introductionmentioning
confidence: 99%
“…5 Further studies demonstrated that the use of an incoherent light source was also efficient in printing a well organized pattern at the surface of an azopolymer thin film. 6 Li et al 7 have decreased the size of the surface exposed to light by using colloidal spheres of azopolymer. Light irradiation could deform the azopolymer colloidal nanospheres.…”
mentioning
confidence: 99%